Computer active control of damping fluid of a racing superbike suspension scheme for road-safety improvement spin-off. (16th September 2008) - Marretta, R.M.A.; Marino, F.; Bianchi, P.
Through tests on a full-scale model setup and the theoretical approach of a non linear 8th-order suspension scheme, this study gives enhancement of the damping fluid active control on the feedback branch of the entire control system for significant improvement of the suspension response to typical road inputs. The fluid flow in suspension dampers shall be conveniently controlled in direction and magnitude by a linear regulator system which is capable to start up – timely concatenated – a solenoid valves-set in order to realize the prescribed relationship between the damping load and the (proportional and time-dependent) variation of fluid flow.